Lathrolestes clypeatus Zetterstedt 1838 - Reshchikov, Alexey (Zenodo, 2015)
Lathrolestes clypeatus (Zetterstedt, 1838) Figs. 19, 21, 31, 61, 62. Tryphon clypeatus Zetterstedt, 1838: 399. Holotype ♀, MZLU [examined]. Type locality: Sweden (Lapland). Lathrolestes eriocraniae Seyrig, 1928: 201. Holotype ♀, MNHN [not examined]. Type locality: France. Material. 2♀, DENMARK, Strandmølle, Boserup, ZMUC; 3♂, DENMARK, Sjaelland, Korsør, ZMUC; 1♀, FINLAND, Lappland, Enontekis, mt. Saana, 27.vi.1962, leg. K.Åhman, (ZMUT, Jussila coll.); 1♀, FINLAND, Lappland, mt. Siilaskoski, 27.vi.1962, leg. K.Åhman, (ZMUT, Jussila coll.); 1♀, FINLAND, Turku, Paattinen, Krouvintie, 92 6787:3244, Malaise trap, 1– 31.5.2004, leg. R. Jussila leg., (ZMUT, Jussila coll.); 1♀, NORWAY, Troms, Storfjord, Skibotn, 29.vi.1962, leg. M.Meinander, (ZMUT, Jussila coll.); 1 ♀, NORWAY, Sør-Trøndelag, Oppland, Kongsvoll, Raubekken, 900m., Øvre, Malaise trap, 03.VII.1980, leg. J. O. Solem, (NTNU); 1♀, NORWAY, Hedmark, Stor-Elvdal, Solbakken, Malaise trap, 24.VI.1986, leg. E. Stur, (NTNU); 1♀, NORWAY, Akerhus, Fetsund, Asak grustak, 25.V.2007, leg. O. Sørlibråten, (ZMUN); 5♀, SWEDEN, Stockholm, NHRS; 10♀, SWEDEN, Torne lappmark, Torneträsk, leg. R.Malaise, NHRS; 11♀, SWEDEN, Lappland, NHRS; 1♀, SWEDEN, Småland, Nybro kommun, Bäckebo, Grytsjöns naturreservat, Old moisty haymaking meadow in forest edge N6311678 E1517066 (=TrapID 1001), 18.v–15.vi.2006 (=coll. event ID 1728), leg. SMTP, NHRS; 1♀, SWEDEN, Uppland, Norrtälje kommun, Svartlöga, Matkrok, Maritime deciduous wood. N59°34.167´E19°03.180´(=Trap ID 26), 27.v–26.vi.2005 (=coll. event ID 1690), leg. SMTP, NHRS; 1♂, SWEDEN, Uppland, Älvkarleby kommun, Marma skjutfält, dry meadow with birch, N60°31.456´E17°27.089´(Trap ID 6), 06.xii.2004 – 03.vi.2005 (=coll. event ID 1578), leg. SMTP, NHRS; 2♀, UK, Scotland, Amat, Easter Ross, NH4689 Malaise trap, native pinewood, 5.89 I. MacGowan, NMSZ, 1992.144; 1♀, UK, Lancashire, Silverdale, Gait Barrows National Nature Reserve, 13.v.1989, leg. M.R.Shaw, RSME; 11♀, UK, 5♂, Cumbria, Witherslack, Strickland Hill, ex. Eriocrania semipurpurella / ...